Effect of seed treatment with QuitoMax® on the yield and quality of ESEN and L-43 varieties of tomato seedlings - Gustavo-González, Luis; Paz-Martínez, Irisneisy; Boicet-Fabré, Tony; Jiménez-Arteaga, María Caridad; Falcón-Rodriguez, Alejandro; Rivas-García, Tomás (REVISTA TERRA LATINOAMERICANA, 2021)
The research work was developed in the basic unit of cooperative production UBPC "Antonio Maceo Grajales" during the 2017-2018 and 2018‑2019 seasons, on a Fluvisol soil, with the objective of evaluating the influence of the QuitoMax® on the seedlings obtained in tomato seedbeds. Two experiments were carried out, in the 2017-2018 season the variety ESEN was evaluated and in the season 2018-2019 the variety L-43, the seeds were soaked in a solution of QuitoMax®, with a concentration of 1 g L-1 during the four hours prior to sowing. Ten polyurethane trays were used for the treated seeds (T1) and another 10 with untreated seeds (T2). At the time of transplantation, the following parameters were evaluated: Plant height (cm), stem thickness (mm), number of leaves, root length (cm) and fresh mass (g). For the statistical analysis of the data from the seedbed, a t-student test was used for a 5% of probability of error, with the statistical package STATISTICA version 8. The results demonstrated the positive incidence of the QuitoMax® about the quality of the seedlings in both varieties.